(untitled) (Academicia Globe: Inderscience Research, 2023)
The improvement of market relations is a process that is accompanied by the decision-making of economic infrastructure. Insurance activities, as an integral part of economic infrastructure, on the one hand, provide social security, and on the other hand, also take on the protection of the interests of the subjects of the economy on the basis of awareness of various insurance risks through contractual obligations and the mechanism of tariffs.